Cultural and hіstorіcal determіnants of the human rіghts attіtudes. Case study : Chіna and the USA - Goncharuk, Mariia-Oleksandra; Lehmannová, Zuzana, 1951-; Peterková, Jana, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2024)
In the global multicultural community, conflicts are oftentimes viewed as caused by an inherent clash of values, norms, and expectations based on those values. In my thesis I intend to discern and compare the historical and cultural factors that contribute to diverse interpretations of the human rights concept between China and the USA, and to examine how these determinants shape the current approaches of these countries to the issue.
Vedoucí práce: Zuzana Lehmannová
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: mezinárodní studia a diplomacie [obor bakal. práce]; bakalářské práce; bachelor's theses